Application of quick tests to identify sexually transmitted infections in a baian municipality: An experience report (Research, Society and Development, 2021)
To reduce the transmission rates and prevalence of sexually transmitted infections (STIs), the application of rapid tests becomes an invaluable tool in tracking and identifying these. Thus, the objective of this work is to describe the experience of applying rapid tests for (ISTs) in an extension activity developed by Pharmacy students, accompanied by a qualified professional, in a public square in the city of Irecê – Bahia. This is a descriptive study of the experience report type. For the action, 50 reagent tests were performed for HIV, Syphilis, Hepatitis B and C in adult individuals. In this process, the participants were asked about their knowledge about the tests and other information about STIs and the responses and postures during the testing were analyzed. Most patients were unaware of the existence of rapid tests, as well as their free of charge in the Sistema Único de Saúde (SUS), there was also a feeling of fear and resistance on the part of some to the test. In addition, prejudiced statements about STIs were also scored, especially regarding the form of transmission. Each participant was instructed on how to prevent it, the importance of carrying out diagnostic tests and where to go if they are exposed to some risky situation. The extension activity made it possible to observe that one of the occupations of the pharmaceutical professional: Transmitting knowledge to the population in the form of continuous education and obtaining positive measurable results.